The feedback related negativity encodes both social rejection and explicit social expectancy violation - Sun, Sai; Yu, Rongjun (Frontiers in Human Neuroscience, 2014)
Humans consistently make predictions about the valence of future events and use feedback to validate initial predictions. While the valence of outcomes provides utilitarian information, the accuracy of predictions is crucial for future performance adjustment. The feedback related negativity (FRN), identified as a marker of reward prediction error, possibly encodes social rejection and social prediction error. To test this possibility, we used event related potential (ERP) techniques combined with social tasks in which participants were required to make explicit predictions (whether others will accept their “friend request” or not, Experiment 1) or implicit predictions (whether they would like this person or not, Experiment 2) respectively, and then received social feedback. We found that the FRN is sensitive to social rejection and explicit social prediction error in Experiment 1 but not implicit social prediction error in Experiment 2. We conclude that the FRN encodes social rejection and explicit social expectancy violation.